Study on influencing factors of particle emissions from a RCCI engine with variation of premixing ratio and total cycle energy. (1st July 2020) - Han, Weiqiang; Lu, Yao; Jin, Chao; Tian, Xiaocong; Peng, Yiqiang; Pan, Suozhu; Liu, Haifeng; Zhang, Peng; Zhong, Yingzi
Abstract: Relevant researches have shown that the prolonged Ignition Delay (ID) is always directly related to the reduction in accumulation mode particle (AMP) and the increase in nucleation mode particle (NMP) emission of Reactivity Controlled Compression Ignition (RCCI) engines. However, seemingly opposite results were discovered in our recent experiments. It appears that ID has no decisive effect on particulate emissions in RCCI engines. To study other main factors which together determine particulate emissions, further detailed experiments were carried out in the RCCI engine with variation of premixing ratio (Rp) and total cycle energy (Etotal ). The results show that the formation of engine particles should be divided into in-cylinder and out-of-cylinder processes. Soot agglomerates are mainly formed during in-cylinder process, while the complex materials, finally collected by the particle analyzer, are mainly formed during out-of-cylinder process. Besides, the influencing factors in both in-cylinder and out-of-cylinder processes together determine the formation of particles, such as the maximum combustion temperature (Tmax ), one in-cylinder impact factor, the exhaust gas temperature and the volatile organic fraction (VOF) concentration, two out-of-cylinder impact factors that conspire to produce a decrease in NMP emission and an increase in AMP emission. Highlights: Three unusual phenomena about particle emission are discovered in this paper. Formation of particles is divided into in-cylinder and out-of-cylinder processes. Effect of in-cylinder and out-of-cylinder impact factors on particle emission differs. Ignition delay is of no decisive factor on particle emission from RCCI engine. Unusual phenomena are decided by both in-cylinder and out-of-cylinder impact factors.